The “Space of Reasons” and Digital Public Sphere: Developing Connections in Empirical Research - Maia, Rousiley; Oliveira, Bruna Silveira de; Orlandini, Maiara (AoIR Selected Papers of Internet Research, 2026)
This paper explores the operationalization of Habermas’ concept of the "space of reasons" in empirical research on the digital public sphere. The study engages with contemporary debates on misinformation, polarization, and democratic challenges, analyzing connections and ruptures in political judgment among social actors. Instead of a micro-level analysis, it adopts a macro perspective, considering interrelated institutions and actors. By focusing on substantive reasons, the research examines how arguments and counter-arguments structure public debates and shape political positioning. The study proposes developing and validating a comprehensive taxonomy of arguments on controversial issues, such as feminist mobilizations and anti-feminist discourse in podcasts and social media. Artificial Intelligence (AI) is employed to systematize and analyze these discourses, following methodologies previously applied in research on climate change and misinformation, for example. Unlike fragmented classifications, this approach seeks a holistic understanding, integrating discursive practices with institutional structures and the actors involved. The paper follows three key steps: (i) it explores the feasibility of applying the "space of reasons" concept in empirical research to systematize the circulation of reasons; (ii) it integrates reasoning practices into a broader network of multiple factors and relationships; (iii) it demonstrates how mapping substantive reasons enhances the understanding of intolerant, extremist, and authoritarian discourses. The study contributes to research agendas on public discourse and conflict dynamics, highlighting methodological and normative challenges in transitioning from micro to macro-level analysis, particularly in a digital environment that is reshaping investigative paradigms.